2018
DOI: 10.29244/jsil.3.1.11-24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Struktur Gedung X di Jakarta Berdasarkan SNI 03-1726-2012 Ketahanan Gempa untuk Struktur Gedung

Abstract: Earthquake risk in Jakarta is the intermediate category in Indonesia based on the 2010 seismic hazard map published by the Ministry of Public Works, Republic of Indonesia. It was important to know the condition of the building that would be affected by earthquake load and to prevent collapse of the building structures that could cause loss of live people in the building and the collisions between buildings. The purpose of this research was to know the ultimate performance limit of the existing X building in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Salah satu cara untuk mengurangi konsumsi energi adalah dengan membangun gedung yang lebih efisien secara energi [1]. Berdasarkan data terbaru yang dipublikasikan oleh Badan Standar Nasional Indonesia (SNI) 1726 -2012 tentang seismik sejak Indonesia termasuk dalam negara rentan gempa berkekuatan besar, ditunjukkan platform atau kondisi gerak ekstrim percepatan di tanah dari banyak tempat di Indonesia jika diklasifikasi bisa kelas desain seismik D, E, atau F, yang dapat sangat mempengaruhi tindakan pekerjaan teknik sipil atau tempat lain struktur bangunan, dan bisa sangat berisiko runtuh dan mengancam jiwa manusia [2].…”
Section: Pendahuluanunclassified
“…Salah satu cara untuk mengurangi konsumsi energi adalah dengan membangun gedung yang lebih efisien secara energi [1]. Berdasarkan data terbaru yang dipublikasikan oleh Badan Standar Nasional Indonesia (SNI) 1726 -2012 tentang seismik sejak Indonesia termasuk dalam negara rentan gempa berkekuatan besar, ditunjukkan platform atau kondisi gerak ekstrim percepatan di tanah dari banyak tempat di Indonesia jika diklasifikasi bisa kelas desain seismik D, E, atau F, yang dapat sangat mempengaruhi tindakan pekerjaan teknik sipil atau tempat lain struktur bangunan, dan bisa sangat berisiko runtuh dan mengancam jiwa manusia [2].…”
Section: Pendahuluanunclassified
“…One way to address this is by constructing buildings that are more energy-efficient (Kumala et al, 2021). Based on the latest data published by the Indonesian National Standardization Agency (SNI) 1726 -2012 regarding seismicity, since Indonesia is classified as a country prone to major earthquakes, it is indicated that the platform or extreme ground motion conditions in many places in Indonesia can be classified as seismic design classes D, E, or F. These conditions can significantly impact engineering actions in civil works or other building structures and pose a high risk of collapse, endangering human life (Fauzan & Sapei, 2018).…”
Section: Introductionmentioning
confidence: 99%